2012
DOI: 10.3109/0142159x.2012.652243
|View full text |Cite
|
Sign up to set email alerts
|

Student perspectives on assessment: Experience in a competency-based portfolio system

Abstract: Despite considerable evidence recognizing the importance of learners' perceptions of the assessment process, there is little literature depicting the participants' experience. We aim to capture these perceptions in order to gain insights into the strengths and weaknesses of a competency-based assessment system. Cleveland Clinic Lerner College of Medicine has implemented a learner-centered portfolio assessment system built around competency standards and continuous formative feedback. Promotion of students is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 10 publications
0
59
0
5
Order By: Relevance
“…Activity systems of the mentoring process. Davis et al 2009;Altahawi et al 2012). Studies on the mentors' perspective showed that mentors learned themselves and benefited in terms of improved interviewing skills, and job satisfaction (Connor et al 2000;Allen & Eby 2003;Eby & Lockwood 2005;Overeem et al 2010), as well as learning not to solve problems for the mentee, and dealing with tensions if the portfolio was assessed (Anderson & DeMeulle 1998;Overeem et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Activity systems of the mentoring process. Davis et al 2009;Altahawi et al 2012). Studies on the mentors' perspective showed that mentors learned themselves and benefited in terms of improved interviewing skills, and job satisfaction (Connor et al 2000;Allen & Eby 2003;Eby & Lockwood 2005;Overeem et al 2010), as well as learning not to solve problems for the mentee, and dealing with tensions if the portfolio was assessed (Anderson & DeMeulle 1998;Overeem et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, if e-portfolios are used to facilitate SDL, learners should receive frequent coaching that complements portfolio use (Altahawi et al, 2012;Kicken et al, 2009b;Welsh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have reported results about coaching. In the Altahawi et al (2012) study students reported that reception of structured feedback early on led them to actively seek feedback later on; furthermore, the provision of formative feedback inspired a gradual shift from deficit thinking towards proficiency strengthening (i.e., moving from experiencing criticism as disciplinary action towards approaching criticism constructively). Similar findings are reported in the Welsh (2012) study that investigated students' perceptions about using an eportfolio to help self-regulate their learning.…”
Section: Learning Process Factorsmentioning
confidence: 99%
See 2 more Smart Citations